تنبيه بشأن النوع الاجتماعي: أصوات القوة: مساهمات المنظمات التي تقودها المرأة الفلسطينية في الاستجابة الإنسانية في الأرض الفلسطينية المحتلة - United Nations Women (United Nations, 2024)
The war on Gaza has become one of the world’s most brutal man-made humanitarian crises. The war has directly impacted more than 2.2 million people, resulting in an unprecedented number of civilians killed, alongside overwhelming displacement. Since 7 October 2023, more than 36,000 Palestinians have been killed by Israeli forces in Gaza, including at least 10,000 women, and an estimated 82,000 people have been injured. The Israeli incursion into Rafah has led to the displacement of nearly 800,000 people since May 2024, many of whom had already been displaced multiple times since October 2023. In tandem, the situation in the West Bank, including East Jerusalem, has also deteriorated, with more than 500 people killed and 5,000 injured since 7 October. As the death toll increases, severe humanitarian needs continue to grow at an unprecedented rate, in a context where needs were already dire before the current escalation. The war on Gaza remains, among other things, a war on women. Over the past eight months of the war, UN Women has been documenting how the lives of women and girls have deteriorated across sectors, including food security, water, shelter, health, and safety. This Gender Alert is on the work of Women-Led Organizations (WLOs).